Podocyte Autophagy: A Potential Therapeutic Target to Prevent the Progression of Diabetic Nephropathy - Na Liu; Liuqing Xu; Yingfeng Shi; Shougang Zhuang (Journal of Diabetes Research)
Diabetic nephropathy (DN), a leading cause of end-stage renal disease (ESRD), becomes a worldwide problem. Ultrastructural changes of the glomerular filtration barrier, especially the pathological changes of podocytes, lead to proteinuria in patients with diabetes. Podocytes are major components of glomerular filtration barrier, lining outside of the glomerular basement membrane (GBM) to maintain the permeability of the GBM. Autophagy is a high conserved cellular process in lysosomes including impaired protein, cell organelles, and other contents in the cytoplasm. Recent studies suggest that activation of autophagy in podocytes may be a potential therapy to prevent the progression of DN. Here, we review the mechanisms of autophagy in podocytes and discuss the current studies about alleviating proteinuria via activating podocyte autophagy.